Hierarchy of nanoscale graphene wrinkles on compliant substrate: Theory and experiment. (October 2020) - Androulidakis, Charalampos; Koukaras, Emmanuel N.; Sampathkumar, Krishna; Rahova, Jaroslava; Galiotis, Costas; Frank, Otakar
Abstract: Wrinklons, the transition zone where two wrinkles are merged to one, have been observed in various thin films across all scales. For suspended films the evolution of the wrinklon wavelength from the edge can be described by λ ∼ x m, where m is universal. Herein we show experimentally that for graphene wrinklons on a compliant polymer, m is not universal, but varies with the graphene thickness. An analytical model is developed based on energy principles, which shows that the influence of the substrate has to be taken into account. The present analysis can be applied further in all thin films on substrate and provides significant physical insight for the wrinklon phenomenology.